Understanding Vaccine Hesitancy Dynamics: Insights from Northern Mindanao, Philippines - Araune, Paolo; Echeveria, Roviech; Agustin, Racquel Vaneza Kate; Arimao, Mohammad Yasser; Arquisola, Desiree; Astillo, Abigail Joyce; Bagayas, Eula Judea; Cabangca, Lisa Marian; Castrudes, Kean Marc; Ceniza, Ray Laurence; Daniel, Arun; Eduave, Stella Clareze; Flores, Christine; Frago, Kiana Kaye (Alta Dharma Publisher, 2024)
Background & Aim: Amidst the ongoing COVID-19 pandemic, vaccine hesitancy persists, especially within specific demographics. This study delved into vaccine hesitancy among Northern Mindanao, Philippines, residents aged 20 to 64, aiming to understand factors shaping vaccination decisions. Employing the Health Belief Model, the research sought to dispel misconceptions and bolster vaccine uptake through evidence-based public health education and improved communication strategies. By examining socio-demographic variables like age, gender, education, religion, and vaccination status, the study informed targeted interventions for enhancing vaccine acceptance and bolstering community health outcomes. Methods: This study employed a quantitative, descriptive-correlational design and analyzed vaccine hesitancy factors among Northern Mindanao, Philippines residents aged 20 to 64. Stratified sampling ensured representative inclusion across age groups, with a sample size of 372 respondents. Statistical analyses, including F-tests and ANOVA, assessed hesitancy differences, while stringent adherence to data privacy regulations safeguarded participant confidentiality. Results: Among respondents, those aged 51 to 69 exhibited the highest vaccine hesitancy levels, particularly regarding uncertainty and knowledge about COVID-19 vaccines. However, no significant relationship was found between hesitancy levels and age or gender. Conversely, significant disparities in hesitancy were observed concerning educational attainment, religion, and vaccination status. Conclusion: While age, gender, education, and religion are associated with varying levels of COVID-19 vaccine hesitancy, none singularly determine hesitancy. Enhanced education and knowledge about vaccines correlate with decreased hesitancy, emphasizing the necessity of targeted education initiatives. However, significant hesitancy disparities based on vaccination status underscore the ongoing challenge of addressing hesitancy despite reassurances about vaccine safety. Recommendation: Implementing tailored educational programs that address specific concerns related to demographic factors is recommended as a crucial strategy for reducing COVID-19 vaccine hesitancy